Development and characterization of metformin hydrochloride- and glyburide-containing orally disintegrating tablets. (13th September 2020) - Gulsun, Tugba; Akdag, Yagmur; Izat, Nihan; Cetin, Meltem; Oner, Levent; Sahin, Selma
Abstract: Diabetes is characterized by chronic hyperglycemia. Although metformin hydrochloride (MHCl)- and glyburide (GLB)-containing conventional tablets are available in the market and used to treat diabetes, orally disintegrating tablets (ODTs) containing the combination of these drugs are not commercially available. Therefore, the aim of this study was to prepare ODTs containing MHCl and GLB by direct-compression (DC-ODTs) and freeze-drying (FD-ODTs) methods. Physical properties of the powder mixture of DC-ODT formulation were determined (Angle of repose: 37.18 ± 1.27°; compressibility index: 20.31 ± 1.06%; Hausner ratio: 1.25 ± 0.03). Its moisture content was 0.3 ± 0.09%. The hardness values and the disintegration times for DC-ODTs and FD-ODTs were 221.60 ± 40.82 and 66.54 ± 2.68 N, and 80 and 30 s, respectively. Friability values were 0.24% for DC-ODTs and 0.38% for FD-ODTs. In uniformity-of-mass for single-dose-preparations test, the average weight was 684.38 ± 1.97 mg for DC-ODTs and 342.93 ± 2.4 mg for FD-ODTs, with less than 5% deviation for all 20 tablets. Water-absorption ratio for DC-ODTs was 1.30 ± 0.05. More than 90% of MHCl and GLB were dissolved within 5 min in both DC-ODTs and FD-ODTs. Although Caco-2 permeability of MHCl was influenced by the ODTs, GLB permeability was not. These results indicated that MHCl- and GLB-containing ODTs may be used as promising formulations for the treatment of diabetes.